A Case of Euglycemic Ketoacidosis Secondary to Continuous Renal Replacement Therapy - Evan J. Chen; William A. West; Kavitha Bagavathy (Case Reports in Critical Care)
Euglycemic ketoacidosis (EKA) has been reported as a rare but life-threatening complication of continuous renal replacement therapy (CRRT). EKA should be suspected in the setting of persistent high anion gap metabolic acidosis despite renal replacement therapy. Critically ill patients, especially those with diabetes mellitus, are at risk of EKA due to deficient caloric intake, the presence of excess counterregulatory stress hormones, and nutritional losses from CRRT. Even with the use of glucose-containing dialysates, EKA can be observed. Prompt treatment with insulin and glucose-containing infusions leads to rapid resolution of the condition. Early optimization of nutritional intake can prevent or mitigate EKA. This case report describes a patient who developed EKA while on CRRT for severe acute kidney injury from neuroleptic malignant syndrome.